TANGGUNGJAWAB PEMERINTAH DAERAH DALAM PELAKSANAAN PROGRAM JAMINAN SOSIAL KETENAGAKERJAAN SEKTOR INFORMAL - La Ode Muhamad Haidar; La Ode Bariun (Universitas Muhammadiyah Mataram, 2021)
This study aims to determine the responsibility of local governments to the implementation of social security for the informal sector. Because in practice, this program is a social insurance system based on contributions paid by participants, and is administered by BPJS Ketenagakerjaan. This type of research is normative legal research, with a statute approach. The legal materials used are primary legal materials, such as statutory regulations and secondary legal materials, such as books and scientific literatures obtained through literature study, which are then analyzed qualitatively. The results of the study indicate that with the existence of regional autonomy and the principle of decentralization, the implementation of social security for employment in the informal sector becomes the authority and responsibility of the regional government. Although universally, the central government also remains responsible for the implementation of social security for employment in the informal sector. The Indonesian state, which has a development model with the concept of a welfare state, is obliged to guarantee and provide protection for the human rights of its citizens, including social protection if its citizens are in a vulnerable situation.Keywords: Local Government Responsibilities, Employment Social Security, Informal. ABSTRAKPenelitian ini ditujukan mengetahui tanggungjawab pemerintah daerah terhadap pelaksanaan jaminan sosial ketenagerjaan sektor informal. Karena secara prakteknya, program ini merupakan sistem asuransi sosial didasarkan pada iuran yang dibayarkan secara oleh peserta, dan diselenggarakan oleh BPJS Ketenagakerjaan. Jenis penelitian ini adalah penelitian hukum normatif (normative legal research), dengan pendekatan perundang-undangan (statute approach). Bahan hukum yang digunakan adalah bahan hukum primer, seperti peraturan perundang-undangan dan bahan hukum sekunder, seperti buku-buku dan literature-literatur karya ilmiah yang diperoleh melalui studi kepustakaan, yang kemudian dianalisis secara kualitatif. Hasil penelitian menunjukan bahwa dengan adanya otonomi daerah dan asas desentralisasi, maka pelaksanaan jaminan sosial ketenagakerjaan sektor informal, menjadi kewenangan dan tanggungjawab dari pemerintahan daerah. Meskipun secara universal, pemerintah pusat juga tetap bertanggungjawab atas pelaksanaan jaminan sosial ketenagakerjaan pada sektor informal tersebut. Negara Indonesia yang memiliki model pembangunan dengan konsep negara kesejahteraan “welafare state”, diwajibkan untuk menjamin dan memberikan perlindungan terhadap hak asasi warga negaranya, termasuk perlindungan sosial apabila warga negaranya dalam situasi rentan.